Prenatal Ultrasound Findings of Circumvallate Placenta and Pregnancy Outcomes - Herrera, Christina L.; Chu, Tina M.; Stanteen, Samantha Mendoza; Twichell, Elizabeth C.; Cardona, Jennifer; McIntire, Donald D.; Twickler, Diane M.; Spong, Catherine Y. (American Journal of Perinatology, 2023)
Objective Circumvallate placenta has a suggested association with adverse pregnancy outcomes (antenatal bleeding, placental abruption, preterm birth, emergency cesarean, small for gestational age infants, and stillbirth). The aim was to determine if prenatal diagnosis of circumvallate placenta is associated with these adverse pregnancy outcomes.Study Design Pregnancies with a singleton gestation prenatally diagnosed with circumvallate placenta between January 1, 2012 and March 31, 2021 were identified. Adverse pregnancy outcomes were obtained. Rates of adverse pregnancy outcomes were compared among those with prenatally diagnosed circumvallate placentas to those without this prenatal diagnosis with a 4:1 control matched group. Pregnancies with known fetal anomalies or other placental abnormalities were excluded. Statistical analyses included Student's t-test and Χ2 with p < 0.05 considered significant.Results Prenatal ultrasound findings of circumvallate placenta were seen in 179 pregnant people (0.20% of all anatomic US studies and 0.17% of all deliveries). Diagnosis was made at a mean gestational age of 19.8 ± 2.4 weeks. Adverse pregnancy outcomes were similar between groups.Conclusion Prenatal ultrasound findings of circumvallate placenta do not correlate with adverse pregnancy outcomes. Given overall good prognosis, prenatal diagnosis of circumvallate placenta may not warrant additional surveillance during pregnancy.Key Points
Keywords: circumvallate placenta; prenatal diagnosis; adverse pregnancy outcomes; antenatal bleeding